Bacteremia Caused by Clostridium symbiosum - Elsayed, Sameer (American Society for Microbiology, 2004)
We describe a fatal case of Clostridium symbiosum bacteremia in a 70-year-old man with metastatic colon cancer. Our report is the first, in the world literature, of human infection caused by this microorganism.